PARASITIC CONJOINED TWINS IN PIG - A CASE REPORT - P. Thirunavukkarasu,; S. Ramakrishnan,; R. Sakthivadivu,; C. Nithya, (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A five year old Large White Yorkshire sow gave birth to a conjoined cephalothoracopagus, which was stillborn.